Nutrigenomics. (9th July 2009) - Gomase, V.S.; Tagore, S.
Nutrigenomics deals with studying of molecular relationships between nutrition and the response of genes. Also involves the characterisation of gene products and the physiological function and interactions of these products. Nutrigenomics focuses on the effect of nutrients on the genome, proteome, metabolome and explains the relationship between these specific nutrients and nutrient-regimes on human health. Nutrigenomics are widely used for studying heart-related disorders as well as diet-related disorders.